POSSIBILITY OF USING CLOUD TECHNOLOGY IN THE EDUCATIONAL AND SOCIAL AREA - Sablina, Mylana A. (Educological discourse, 2014)
Nowadays, society is in the transition to an information society. Therefore, the formation of the information society questions in educational institutions and institutions social area. The article discusses the possibility of using cloud technology in the social area, the perspectives of transition to the cloud network outlined in future, the main advantages and disadvantages of their introduction showed. The analysis results of new studies of transition of educational institutions and organizations to the cloud service.